PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA BALI MITRA WAHANA RAFTING DI KABUPATEN KARANGASEM - Ni Kadek Ekayanti; I Putu Bagus Suthanaya (Journal Research of Management, 2020)
This research aims to determine the influence of communication on the performance of employees of Bali Mitra Wahana Rafting in Karangasem Regency, knowing the influence of work discipline on employee performance, knowing the influence of communication and work discipline on employee performance, knowing the great influence of communication and working discipline on employee performance and knowing the free variables that are dominant influence on employee performance in Bali Mitra Wahana Rafting in Karangasem regency. In this study, used as a sample is the employee of Bali Mitra Wahana Rafting in Karangasem regency. The sampling techniques in this study using the population method are the sampling methods of all popoulation for accurate data for research purposes. The analytical techniques used were regression analyses with hypothesis testing using the F test and T test. The results showed that communication and work discipline were influential in employee performance of employees. Communications partially have a positive and significant influence on employee performance.Work disciplines partially have a positive and significant influence on employee performance. Communication and work discipline simultaneously have a positive and significant influence on the performance of Employees in Bali Mitra Wahana Rafting in Karangasem regency, this is analyzed simultaneously, can be proved through a regression coefficient of communication and work discipline on the performance of Employees Bali Wahana Rafting in Karangasem regency.